Lifestyle changes after retirement: a Grounded Theory - Sonia Silva Marcon; Verônica Francisqueti Marquete; Thiago Privado da Silva; Mayckel da Silva Barreto; Maria do Carmo Fernandez Lourenço Haddad; Helena Maria Almeida Macedo Loureiro; Vitoria Vasconcelos Logullo; Sueli Mutsumi Tsukuda Ichisato (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to understand the changes that occur in professors’ lifestyle after retirement with regard to self-care. Methods: qualitative research that used Symbolic Interactionism as a theoretical framework and Grounded Theory, a constructivist approach, as a methodological framework. Data were collected in 2022, through remote interviews with 18 professors from a public university in northwestern Paraná. Results: with retirement, professors have greater availability and flexibility in their schedules, favoring positive changes in lifestyle, with greater appreciation of self-care actions, such as physical exercise and healthy eating, taking care of appearance, stimulating memory, a more active social life and adopting hobbies, expressed in the category “Enjoying retirement and taking up new activities”. Final considerations: retired professors, influenced by their social interactions with friends, family, healthcare professionals and co-workers throughout their lives, at this particular stage, tend to value self-care more.